Patient reported outcome data as performance indicators in surgically treated lung cancer patients. (April 2019) - Brønserud, Majken M.; Iachina, Maria; Green, Anders; Groenvold, Mogens; Jakobsen, Erik
Highlights: Even in a small country, large differences between subpopulations are present. Surgical resection extent is not associated with postoperative Global Health Status. Surgical access type is not associated with postoperative Role Function. It is feasible to use PROs as outcome indicators after lung cancer surgery. Abstract: Objective: Quality in lung cancer care is in Denmark routinely evaluated using quality indicators. The indicators are reported from national registries and are based on data from health care professionals. However, data based on the patients' perspective are rarely reported. The aim of this study was to propose a model for the use of patient reported outcomes (PROs) as quality indicators, enabling us to compare PROs across the surgical departments in Denmark. Methods: All patients registered in the Danish Lung Cancer Registry (DLCR) from 1 October 2013 until 30 September 2015 who received surgical treatment were eligible (N = 1718). They were asked to complete the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 questionnaire six months after surgery. From QLQ-C30 we chose global health status (GHS) and role function (RF) as indicators to be tested. An indicator threshold for good performance was set to ≥ 65 points (on a scale 0–100 where 100 was the best). Results were compared between the four thoracic surgical departments in Denmark. Results: Of 1615 patients alive six months after surgery, questionnaires were completed by 1002 patients (62.0%). The patients from the four departments differed significantly in clinical variables at diagnosis, and the departments differed significantly in the surgical procedures performed. After adjustment for case-mix, the patients in Department 2 had a better RF than patients from the other departments. Conclusion: Significant differences in RF and in the fulfilment of the indicator requirement for RF were observed. Since these findings might indicate differences in the quality of performance between participating departments, subsequent audit is recommended. The analyses and results indicate that it is feasible to use PROs as supplementary outcome indicators in the evaluation of the quality of surgical treatment for lung cancer. Our model could serve as a useful foundation for further research.